Exploring beyond clinical routine SARS-CoV-2 serology using MultiCoV-Ab to evaluate endemic coronavirus cross-reactivity - Matthias Becker (Nature Portfolio, 2021)
Serology is an important way to monitor SARS-CoV-2 infection in the population and support vaccine development. Here the authors develop a multiplex immunoassay including spike and nucleocapsid proteins of SARS-CoV-2 and the endemic human coronaviruses with high specificity and sensitivity.